Review of the philosophy of science on the development of resistant starch from mas bananas as a functional food supporting food security - Siska Cicilia; Muhammad Sarjan; Arifuddin Sahidu; Amrullah; Moegiratul Amaro; Mutia Devi Ariyana; Ida Ayu Widhiantari; Husnul Jannah; Sudarli; Hanifah Ayu; Aida Muspiah; Gunawan (Journal of Food and Agricultural Product, 2026)
The rising prevalence of degenerative diseases in Indonesia, such as hypertension and diabetes mellitus, is closely associated with dietary shifts toward high fat, sugar, and low fiber consumption. One crucial preventive effort is the development of functional foods, especially resistant starch, which helps improve glycemic response, gut health, and metabolic profiles. This study aims to assess the development potential of resistant starch from mas banana as a functional food to support national food security. The research method was a qualitative literature review, analyzing scientific publications on the characteristics, synthesis, application, and benefits of resistant starch from mas banana. Results reveal that resistant starch from mas banana can be produced through physical, chemical, and enzymatic modifications, yielding superior starch properties which not only provide beneficial physiological effects but also have the potential to substitute imported wheat-based products. The development of functional foods based on mas banana resistant starch is scientifically relevant and an axiological strategy to strengthen food security by diversifying local carbohydrate sources. Keywords: food security, functional food, mas banana